The Effect of Combustion Temperature On Exhaust Gas Emissions : New multi-level drum municipal solid waste incinerator - I Putu Angga Yuda Pratama; I Nyoman Suprapta Winaya; I Wayan Arya Darma; Kadek Dwi Wahyuadnyana (International Journal of Science and Environment (IJSE), 2026)
Municipal solid waste (MSW) is a crucial problem in today's era where the growth of waste production continues to increase every year. One of the most effective thermal technologies used to reduce the volume of waste is through the incineration process. Incineration is the thermal-induced oxidation of waste to transform solid waste into inert ash and also sterilize or destroy hazardous chemicals and biological agents. A new multi-level drum incinerator was designed and fabricated with a plate thickness of 2 mm and a combustion chamber volume of 0.15 m3 and a height of 4 meters made from a drum with a diameter of 60 cm and coated with 5 cm thick refractory. During the incineration process of MSW, the incinerator emits exhaust gases or pollutants such as NOx, SO2, HCl, CO, and dioxins, which are harmful to the environment. To reduce the production of these pollutants, a suitable combustion temperature is required to ensure that MSW is well converted. In this study, the combustion temperatures were set at 450o, 500o, 550o, and 600oC. After testing, the lowest pollutant results were obtained at a combustion temperature of 600oC, with an average production of CO and CH4 of 0.29% and 0.120%, respectively. At this temperature, the combustion process occurs more quickly, and the measured combustion temperature profile is more stable, thus reducing the production of incinerator exhaust gases.